Abecedário: educação da diferença - de Menezes, Antonio Basilio Novaes Thomaz (Educação & Realidade, 2010)
AQUINO, Julio Groppa; CORAZZA, Sandra Mara (Org.). Abecedário: educação da diferença. Campinas, SP: Papirus, 2009.